Sanctions For Non-Performing Corporate Social Responsibility - Jaya, Febri; Hutauruk, Rufinus Hotmaulana; Rusdiana, Shelvi (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Companies are legal materials that have a role in national development. Its role can be realized by carrying out corporate social and environmental responsibilities as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies. However, many companies neglect this responsibility.Purposes of the Research: The purpose of this study is to analyze the sanctions related to companies that do not carry out these responsibilities.Methods of the Research: The method in this research is normative juridical. In this study also used literature study. In terms of reviewing this research, a judical basis was used which consisted of Law Number 40 of 2007 and Government Regulation Number 47 of 2012.Results of the Research: Based on the results of the research, it was found that the laws and regulations governing corporate social and environmental responsibility have a legal vacuum, namely that there are no clear sanctions for companies that do not carry out these responsibilities. The urgency of regulation is sanctions because by not regulating sanctions, there is an ambiguity of norms that will lead to legislative law.